'Acidaminococcus timonensis' sp. nov. and 'Acidaminococcus massiliensis' sp. nov. isolated from human gut. (January 2017) - Ricaboni, D.; Mailhe, M.; Benezech, A.; Cadoret, F.; Fournier, P.-E.; Raoult, D.
Abstract: We report here the main characteristics of 'Acidaminococcus timonensis' strain Marseille-P2764 T, isolated from human right colon, and 'Acidaminococcus massiliensis' strain Marseille-P2828 T, isolated from human duodenum.